Health, functioning and accessibility among spinal cord injury population in Finland: Protocol for the FinSCI study - Susanna Tallqvist; Heidi Anttila; Mauri Kallinen; Eerika Koskinen; Harri Hämäläinen; Anna-Maija Kauppila; Anni Täckman; Aki Vainionpää; Jari Arokoski; Sinikka Hiekkala (Medical Journals Sweden, 2019)
Background and purpose: The purpose of the Finnish Spinal Cord Injury Study (FinSCI) is to identify factors related to the health and functioning of people with spinal cord injury, their challenges with accessibility, and how such factors are interconnected. The International Classification of Functioning, Disability and Health (ICF) is used as a structured framework in the study. Design: Protocol of mixed methods study. Results: Study participants were recruited from all 3 SCI outpatient clinics in Finland. The final target group consists of 1,789 subjects with spinal cord injury. The final questionnaire was formed from 5 different patient-reported instruments. The spinal cord injury-specified instruments are the Spinal Cord Injury Secondary Condition Scale, the Spinal Cord Independence Measure, and the Nottwil Environmental Factors Inventory Short Form. In addition, questions from the following generic instruments were chosen after a selection process: the Patient-Reported Outcomes Measurement Information System, PROMIS®, and the National Study of Health, Well-being and Service, FinSote. Altogether, the final questionnaire covers 64 ICF categories and consists of 151 ICF-linked questions. Conclusion: The formulated questionnaire covers widely different aspects of health, functioning and accessibility. The questionnaire results and subsequent interviews will help in developing care and rehabilitation policies and services for people with spinal cord injury.